Analisis Pelaksanaan Pengadaan Dan Penghapusan Barang Milik Daerah - Mislinawati; Mohd. Saadi Nurdin (Program Studi Akuntansi Fakultas Ekonomi Universitas Samudra, 2023)
This research discusses about the implementation of procurement and elimination of regional stufss at Banda Aceh Kesbangpol agency. The aim of this study is to find out the importance of the procedures for implementing stuffs’ procurement and elimination in regional property management activities. This is motivated by considering that the implementation of the procurement and elimination of regional property is the last step towards efforts to control regional property. This problem cannot be taken slightly because if there are stuffs under the management and control of a government agency, they do not pay attention to the issue of elimination, then there will be possible to raise a condition where the incoming stuffs cannot contribute to the implementation of government activities, but burden the maintenance cost, even they are vulnerable to theft.